NATURE-ORIENTED ECO-RECREATIONAL PRACTICES AS A TOOL FOR SUSTAINING THE ECOTOURISM AND BIOTIC POTENTIAL OF BOIKIVSHCHYNA NATIONAL PARK - Zhylishchych , Ю.; Krektun , Б.; Wiesinger , Г.; Khirivskyi , П.; Salamakha , І.; Panas , П.; Hermanovych , О.; Korinets , Ю. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The conducted research confirms that under increasing anthropogenic pressure and climate change, national nature parks acquire strategic importance in maintaining ecological balance, conserving biodiversity and unique natural complexes, shaping environmental awareness, supporting the development of ecological recreation, and fulfilling socio-rehabilitation functions. The Boikivshchyna National Nature Park plays a significant role as a multifunctional nature conservation area and a space for ecotourism, forest therapy, hydrotherapy, and social rehabilitation. The park’s ecosystems are distinguished by the richness of their biotic resources, with over 1,000 animal species, including rare predators, and more than 700 vascular plant species, 32 of which are listed in the Red Book of Ukraine. Forest landscapes and natural waters of mountain rivers and springs possess substantial therapeutic potential. The research has confirmed the positive impact of natural landscapes on the psycho-emotional state of individuals. The article analyzes the prospects for developing sensory-based wellness methodologies founded on the use of the park’s floristic environment as a component of forest therapy practices. Additionally, it is shown that Boikivshchyna NNP applies elements of forest pedagogy and environmental education, particularly through the development of thematic ecological trails, interactive lessons, workshops, environmental classes, and community campaigns. The article outlines the potential for the park’s integration into regional sustainable development processes, social adaptation of war-affected populations, and the implementation of European Green Care practices and nature-based wellness spa concepts. The need for continued interdisciplinary collaboration among scientists, ecologists, and local communities is emphasized to ensure effective use of the park’s recreational and conservation potential.